(REVISITING) ALLOMORPHISMS IN CORPORATIONS AND HRM IN INFORMATIONAL SOCIETY (Revista Lusófona de Economia e Gestão das Organizações, 2018)
The informational society is not innocuous for corporations and organizations. The assortment of allomorphic phenomenon that are taking place in corporations and on the implicit human resources management (i.e. persons) cannot set aside any indifference among entrepreneurs, workers or social partners. The corporation’s frameworks, the structure and performance, the person’s management, the labour relations and other new dimensions are analyzed on the present paper, trying to preview some tendencies.We make an attempt to shape the behaviors and forthcoming procedures of the social actors in order to forecast the management and the labour, with the certainty that the uncertainty is part of the future.Key-words: informational society; allomorphisms; changing; trends; organizations; corporations; globalization